2018
DOI: 10.23969/planologi.v5i1.929
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Pengelolaan Sampah Oleh Masyarakat Di Kawasan Perkotaan Ciwidey

Abstract: Kawasan Perkotaan Ciwidey sebagai pusat kegiatan perkotaan tidak terepas dari permasalahan terkait persampahan yaitu peningkatan timbulan sampah setiap harinya tidak diimbangi dengan adanya sarana dan prasarana pengelolaan sampah. selain itu aksesibilitas yang cukup jauh menghambat pendistribusian sampah dari Kawasan Perkotaan Ciwidey ke TPA. Untuk itu penelitian ini bertujuan untuk merumuskan arahan terkait pengelolaan sampah dengan berdasarkan kepada masyarakat (berbasis masyarakat) sebagai sumber penghasil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this representation process, it can also be known that household communities are still lacking in participation in managing waste such as not sorting waste according to its type, and only a few household communities sort waste before it is disposed of in the containers provided. The results of this study are in line with the study conducted by [11], that there is still a lack of community participation in carrying out waste management by such as sorting, the community only throws waste into one container without sorting as has been urged by the cleaners. It can be concluded that the waste storage process is still not in accordance with existing policies, where the available household housing places do not have disaggregated trash cans according to their types such as wet garbage and kerisng waste mixed into the same container, and the trash cans are also inadequate in accordance with applicable regulations, namely they must be closed.…”
Section: Discussionsupporting
confidence: 86%
“…In this representation process, it can also be known that household communities are still lacking in participation in managing waste such as not sorting waste according to its type, and only a few household communities sort waste before it is disposed of in the containers provided. The results of this study are in line with the study conducted by [11], that there is still a lack of community participation in carrying out waste management by such as sorting, the community only throws waste into one container without sorting as has been urged by the cleaners. It can be concluded that the waste storage process is still not in accordance with existing policies, where the available household housing places do not have disaggregated trash cans according to their types such as wet garbage and kerisng waste mixed into the same container, and the trash cans are also inadequate in accordance with applicable regulations, namely they must be closed.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding Cresswell (2010), mixed methods are two forms of methods that are mutually integrated in combining, linking, and unifying data, where this study begins with qualitative data collection and analysis and then continues with quantitative data collection and analysis. Qualitative data collection can be done by field observations, interviews with related parties, literature, and policy studies (Suntari, 2018). Meanwhile, quantitative data were carried out using a questionnaire survey method to 319 units of waste bank and 423 people in Depok City.…”
Section: B Methodsmentioning
confidence: 99%
“…Depok City, as one of the satellite cities located to the south of Jakarta Capital City has an area of 200.29 km 2 and a population of 2,056,335 people in the year 2020 (BPS, 2021). Population growth and socio-economic activities in urban areas naturally correlate with rising in both the amount and type of waste generated (Suntari et al, 2018). Regarding data from Environmental Agency (DLHK) of Depok City, waste production in Depok City every day is about 1,565 tons.…”
Section: Introductionmentioning
confidence: 99%
“…According to Puspa (2017) The organic waste management process can involve several steps, starting with waste collection in containers at the producer followed by temporary storage, transportation, and finally processing and recycling at a facility that can use composting, burning, landfilling, or other methods.…”
Section: Dangerous Wastementioning
confidence: 99%